The Effect of Self Efficacy and Parent Support on Learning Motivation in Management Business Students in Padang's Private Vocational School - Hasanah, Ummul; Alizamar, Alizamar; Marjohan, Marjohan; Engkizar, Engkizar (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2019)
This study departs from the expectation that high or low student learning motivation are influenced by self-efficacy and family environment. The results of the study show that: 1) self-efficacy has a significant effect on learning motivation. 2) self-efficacy and parental support have a significant effect on learning motivation. This research is an associative descriptive study. The sample in this study is the business management students of class X and XI that are registered at Padang Private Vocational School. The findings from this study are expected to be a reference for teachers and other academic communities to be able to pay more attention to students in learning by giving attention to the family environment and paying attention to their learning attitudes and also help increase student motivation in learning so that maximum learning outcomes are obtained